2001
DOI: 10.2169/internalmedicine.40.697
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Prognosis in Adult IgA Nephropathy, Especially with Mild Proteinuria or Mild Histological Features.

Abstract: Objective The present study was undertaken to clarify the clinical course and prognosis of adult patients with primary IgA nephropathy (IgAN), especially with mild pro-teinuria or mild histological alternations. Patients and Methods A population of 735 IgAN patients whomwe were able to observe for morethan two years was examined. Results A total of 115 patients (15.6%) was on dialysis during the observation period. The overall 5-year renal survival rate was 92.0%. On the other hand, 166 patients (22.6%) were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 11 publications
0
19
0
1
Order By: Relevance
“…These studies included a relatively large number of patients with hypertension or renal insufficiency at biopsy, which was not the case in the aforementioned studies (7,8). In Usui's study (21), renal histopathology showed severe mesangial involvement or glomerular sclerosis in 6.1% of 197 patients. In Szeto's study (6), severe renal injury was observed in 12.5% of 72 patients.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…These studies included a relatively large number of patients with hypertension or renal insufficiency at biopsy, which was not the case in the aforementioned studies (7,8). In Usui's study (21), renal histopathology showed severe mesangial involvement or glomerular sclerosis in 6.1% of 197 patients. In Szeto's study (6), severe renal injury was observed in 12.5% of 72 patients.…”
Section: Discussionmentioning
confidence: 92%
“…Recently, however, two studies on IgAN with mild proteinuria have shown contradictory results (6,21). These studies included a relatively large number of patients with hypertension or renal insufficiency at biopsy, which was not the case in the aforementioned studies (7,8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For early detection of glomerulonephritis, urinalysis has been considered one of the best methods [35,36]. The level of proteinuria is one of the strongest predictors for renal function deterioration [24,[37][38][39][40][41]. Consequently, to prevent an increase in the number of ESRD patients in Japan, a dipstick urine examination has been continued under the auspices of local governments and the Ministry of Health, Labor and Welfare of Japan since 1972 [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, it was the most attractive low, but those percentages cannot be disregarded in daily clinical treatment.The most important point is how do we find these patients with unexpected-prognosis and prevent the decline of renal function of those patients. Usui et al (24) …”
mentioning
confidence: 99%